A new optimal reactive power scheduling method for loss minimization and voltage stability margin maximization using successive multi-objective fuzzy LP technique - Venkatesh, B.; Sadasivam, G.; Khan, M.A. (IEEE transactions on power systems, 2000)
Insufficient reactive power support in a power grid results in under voltages at load centres and also limits the real power transfer capacities of the transmission systems leading to voltage collapse. An optimal reactive power scheduling method is sought which minimizes real power transmission loss and maximizes voltage stability margin (VSM) subject to the utmost satisfaction of all the violated load bus voltage constraints. A multi-objective fuzzy LP (MFLP) method of solution in the successive LP (SLP) framework is proposed to solve the problem. A set of least singular values of the load flow Jacobian is used as VSM indicator. This set is expressed in terms of the control vector and is maximized in the proposed formulation to maximize VSM. Results of the tests of the proposed method on modified IEEE 6 bus and 57 bus systems are presented. The changes in the load flow Jacobian singular values during scheduling are studied.